2022
DOI: 10.7759/cureus.21857
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surgical Outcome in Three- and Four-Part Proximal Humerus Fracture Treated With Proximal Humerus Internal Locking System (PHILOS) Plate Versus Neer’s Prosthesis in Elderly Patients

Abstract: Background: With an incidence of 50% of humerus fractures, proximal humerus fractures (PHFs) can significantly impact one's quality of life. Moreover, management of highly comminuted or displaced PHFs poses a significant challenge amongst elderly population due to poor bone quality. Prosthetic replacement of humeral head or its stabilization using external plates is a commonly employed intervention for treating three-and four-part PHFs. Thus, these two methods were compared in this study to identify a preferab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the present research, the functional outcome after 6 months follow up, 10 19 . Other researchers have also shown that PHILOS plate is useful in majority of fractures with help of correct surgical technique.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the present research, the functional outcome after 6 months follow up, 10 19 . Other researchers have also shown that PHILOS plate is useful in majority of fractures with help of correct surgical technique.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, the injury was implicated by simple fall and fall from height in 36.7% patients, 6.7% had physical assault and 56.7% had fracture because of road traffic accidents. In a study presented from UK by the Gaheer et al, mechanism of injury was fall in 78.6% patients while 12 (21.4%) patients had road-traffic accidents 12 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous study showed comparable results. [20] Plate-and-screw fixation is commonly used to treat proximal humeral fractures, however it has been related to complications such as screw pullout in osteoporotic bone, subacromial friction, and avascular necrosis of a humeral head from extensive periosteal stripping. [21] There is a significant rate of fixation failure after T-buttress plates are used for proximal humeral fractures, according to research by Kristiansen and Christensen.…”
Section: Neer's Classificationmentioning
confidence: 99%